Animating in real time using virtual and augmented reality tools (2019)
This paper discusses an inexpensive alternative to animating 3D humanoid models in real time, something used in the film and gaming industry very frequently. The basic concept is to use already existing AR and VR tools, some which are already very accessible in today's market, to animate the model's body and face.